Valproic acid attenuates manganese-induced reduction in expression of GLT-1 and GLAST with concomitant changes in murine dopaminergic neurotoxicity - Johnson, James (Neurotoxicology, 2018)
Exposure to elevated levels of manganese (Mn) causes manganism, a neurological disorder with similar characteristics to those of Parkinson’s disease (PD). Valproic acid (VPA), an antiepileptic, is known to inhibit histone deacetylases and exert neuroprotective effects in many experimental models of neurological disorders. In the present study, we investigated if VPA attenuated Mn-induced dopaminergic neurotoxicity and the possible mechanisms involved in VPA’s neuroprotection, focusing on modulation of astrocytic glutamate transporters (glutamate aspartate transporter, GLAST and glutamate transporter 1, GLT-1) and histone acetylation in H4 astrocyte culture and mouse models. The results showed that VPA increased promoter activity, mRNA/protein levels of GLAST/GLT-1 and glutamate uptake, and reversed Mn-reduced GLAST/GLT-1 in in vitro astrocyte cultures. VPA also attenuated Mn-induced reduction of GLAST and GLT-1 mRNA/protein levels in midbrain and striatal regions of the mouse brain when VPA (200 mg/kg, i.p., daily, 21 d) was administered 30 min prior to Mn exposure (30 mg/kg, intranasal instillation, daily, 21 d). Importantly, VPA attenuated Mn-induced dopaminergic neuronal damage by reversing Mn-induced decrease of tyrosine hydroxylase (TH) mRNA/protein levels in the nigrostriatal regions. VPA also reversed Mn-induced reduction of histone acetylation in astrocytes as well as mouse brain tissue. Taken together, VPA exerts attenuation against Mn-induced decrease of astrocytic glutamate transporters parallel with reversing Mn-induced dopaminergic neurotoxicity and Mn-reduced histone acetylation. Our findings suggest that VPA could serve as a potential neuroprotectant against Mn neurotoxicity as well as other neurodegenerative diseases associated with excitotoxicity and impaired astrocytic glutamate transporters.